2012
DOI: 10.1155/2012/180379
|View full text |Cite
|
Sign up to set email alerts
|

Tilted Implants for Full-Arch Rehabilitations in Completely Edentulous Maxilla: A Retrospective Study

Abstract: Purpose. The aims of this study were to assess the treatment outcome of immediately loaded full-arch fixed bridges anchored to both tilted and axially placed implants in the edentulous maxilla and to evaluate the incidence of biological and prosthetic complications. Materials and Methods. Thirty-four patients (18 women and 16 men) were included in the study. Each patient received a maxillary full-arch fixed bridge supported by two axial implants and two distal tilted implants. A total of 136 implants were inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 21 publications
1
47
1
1
Order By: Relevance
“…All studies but two 16,52 provided information of the patients' age, and none of them included non-adults patients. Some patients in thirty-three studies 1, 3,7,8,14,15,17,18,[20][21][22][23][24][25][27][28][29][30][32][33][34]36,[40][41][42][44][45][46][47][48][49]51,52 were smokers. Five studies 16,42,44,46,49 reported the presence of bruxers among the patients, and six studies 1, 28,42,46,48,49 the presence of diabetic patients.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies but two 16,52 provided information of the patients' age, and none of them included non-adults patients. Some patients in thirty-three studies 1, 3,7,8,14,15,17,18,[20][21][22][23][24][25][27][28][29][30][32][33][34]36,[40][41][42][44][45][46][47][48][49]51,52 were smokers. Five studies 16,42,44,46,49 reported the presence of bruxers among the patients, and six studies 1, 28,42,46,48,49 the presence of diabetic patients.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…In twenty-three studies 1, 3,8,16,18,21,22,[24][25][26][27][28]30,31,35,39,42,45,46,[48][49][50]52 the patients were exclusively rehabilitated with fixed full-arch prostheses receiving 2 distal tilted implants and 2 mesial axially placed implants. Patients were submitted to grafting procedures at the implant site in only two studies.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations